Sensitivity of Upper Atmosphere to Different Characteristics of Flow Bursts in the Auroral Zone. Issue 10 (12th October 2021) - Sheng, Cheng; Deng, Yue; Gabrielse, Christine; Lyons, Larry R.; Nishimura, Yukitoshi; Heelis, Roderick A.; Chen, Yun‐Ju
Abstract: Meso‐scale plasma convection and particle precipitation could be significant momentum and energy sources for the ionosphere‐thermosphere (I‐T) system. Following our previous work on the I‐T response to a typical midnight flow burst, flow bursts with different characteristics (lifetime, size, and speed) have been examined systematically with Global Ionosphere‐Thermosphere Model (GITM) simulations in this study. Differences between simulations with and without additional flow bursts are used to illustrate the impact of flow bursts on the I‐T system. The neutral density perturbation due to a flow burst increases with the lifetime, size, and flow speed of the flow burst. It was found that the neutral density perturbation is most sensitive to the size of a flow burst, increasing from ∼0.3% to ∼1.3% when the size changes from 80 to 200 km. A westward‐eastward asymmetry has been identified in neutral density, wind, and temperature perturbations, which may be due to the changing of the forcing location in geographic coordinates and the asymmetrical background state of the I‐T system. In addition to midnight flow bursts, simulations with flow bursts centered at noon, dawn, and dusk have also been carried out. A flow burst centered at noon (12.0 Local Time [LT], 73°N) produces the weakest perturbation, and a flow burst centered at dusk (18.0 LT, 71°N) produces the strongest. Single‐cell and two‐cell flow bursts induce very similar neutral density perturbation patterns. Key Points: Neutral density perturbations due to a midnight flow burst are most sensitive to scale size Neutral density perturbation magnitudes due to flow bursts at different local times depend on the background state Single‐cell and two‐cell flow bursts induce similar perturbation patterns